2020
DOI: 10.1055/a-1177-6814
|View full text |Cite
|
Sign up to set email alerts
|

Effect of KCNH6 on Hepatic Endoplasmic Reticulum Stress and Glucose Metabolism

Abstract: Adult patients with a dysfunctional ether-a-go-go 2 (hERG2) protein, which is encoded by the KCNH6 gene, present with hyperinsulinemia and hyperglycemia. However, the mechanism of KCNH6 in glucose metabolism disorders has not been clearly defined. It has been proposed that sustained endoplasmic reticulum (ER) stress is closely concerned with hepatic insulin resistance and inflammation. Here, we demonstrate that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Our group found that adult patients or mice with dysfunctional KCNH6 gene expression presented with hypoinsulinemia or hyperglycemia [ 12 , 13 ]. Another study revealed that KCNH6 may cause endoplasmic reticulum (ER) stress in the liver and cell apoptosis [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our group found that adult patients or mice with dysfunctional KCNH6 gene expression presented with hypoinsulinemia or hyperglycemia [ 12 , 13 ]. Another study revealed that KCNH6 may cause endoplasmic reticulum (ER) stress in the liver and cell apoptosis [ 14 ].…”
Section: Introductionmentioning
confidence: 99%